Body mass index in girls with idiopathic central precocious puberty during and after treatment with GnRH analogues - Arcari, A. J. (Int J Pediatr Endocrinol, 2016)
BACKGROUND: In girls with Idiopathic Central Precocious Puberty (ICPP) concern has been raised by the potential impact of GnRH-analogues (GnRHa) treatment on body weight. We evaluated the effect of GnRHa on Body Mass Index (BMI) in girls with ICPP according to weight status at diagnosis. METHODS: One hundred seventeen ICPP girls were divided according to pretreatment weight status in: normal weight (NW), overweight (OW) and obese (OB). BMI at one and two years of treatment was assessed. BMI-SDS of 60 patients who reached adult height (AH) was compared to that of 33 ICPP untreated girls. RESULTS: NW girls significantly increased their baseline BMI-SDS at 1 and 2 years of treatment. OW girls only had a significant increment at one year of treatment while OB girls showed no BMI-SDS change. Patients evaluated at AH (at least four years after GnRHa withdrawal) showed a significant decrease on BMI compared to baseline and a significantly lower BMI than the untreated group. CONCLUSION: In ICPP girls the BMI increase under GnRHa was inversely related to the pretreatment weight status. In the long term follow-up, no detrimental effect of GnRHa on body weight was observed. BMI-SDS was lower in treated than in untreated girls.